Governing partnerships for development in post‐conflict settings: Evidence from a longitudinal case study in Colombia. (3rd April 2020) - Pfisterer, Stella; Van Tulder, Rob
Abstract: Drawing on a longitudinal case study of a 10‐year cross‐sector partnership for development in Colombia, this paper makes three contributions to current discussions on new collaborative governance approaches in which business, non‐governmental organizations and development agencies jointly address development challenges. First, our study explores how partnerships can be successful in achieving longer term development while being designed as short‐term governance arrangements. Second, we shed light on how power asymmetries can shape partnership governance. Many studies have highlighted the negative aspects of donor involvement in cross‐sector partnerships. We identify, however, that an interplay of formal and informal governance in partnerships can provide a positive enabling framework for partner relationships to grow and mature. Third, the case highlights that the studied partnership employed governance mechanisms that facilitate local ownership and empower small‐scale farmers, which effected (longer term) value chain relationships. In this regard, our case study helps to understand governance processes and conditions under which transformative local partnerships can emerge and sustain in post‐conflict settings. The paper adds observations on the collaborative governance content that is required for a more integrative research approach to corporate contributions to development.